The association between iliac vein compression degree and characteristics of first diagnosed left lower extremity deep vein thrombosis - Shi, Yadong; Yuan, Yuan; Gong, Maofeng; Su, Haobo; Chen, Liang; Huang, Hao; Lu, Zhaoxuan; Zhou, Yangyi; Gu, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to investigate the association between the left common iliac vein (CIV) compression degree and characteristics of first diagnosed left lower extremity deep vein thrombosis (DVT). Patients and methods: This was a single-center retrospective observational study. Between January 2015 and June 2022, first diagnosed left lower extremity DVT patients with enhanced computed tomography of lower extremities were included. Patient demographics, comorbidities, risk factors, DVT characteristics, and CIV compression degree were collected and analyzed. Logistic regressions were performed to evaluate the odds ratio (OR) with a 95% confidence interval (CI) of iliofemoral or mixed DVT versus compression percentage. The association between compression percentage and iliofemoral or mixed DVT was evaluated on a continuous scale with restricted cubic splines (RCS). The association between compression percentage and thrombus burden was evaluated using the Spearman test. Results: A total of 196 (mean age, 61.8 ± 16.1 years; 86 males) patients were included. The median CIV compression percentage in iliofemoral or mixed DVT patients was significantly greater than in non-iliofemoral or non-mixed DVT, respectively (64.4% vs 46.6%, p < 0.001; 67.8% vs 54.8%, p = 0.004). CIV compression > 50% was associated with significantly increased morbidity of iliofemoral DVT (adjusted OR, 2.96; 95% CI, 1.58-5.52; p = 0.001) or mixed DVT (adjusted OR, 2.39; 95% CI, 1.19-4.81; p = 0.014). RCS showed that a greater compression percentage was associated with a continuously increased OR of iliofemoral DVT (overall p = 0.003, nonlinear p = 0.577) or mixed DVT (overall p = 0.020, nonlinear p = 0.771). CIV compression percentage had a positive correlation with thrombus burden (rs = 0.284, p < 0.001). Conclusions: A greater left CIV compression percentage may be associated with increasing risk of more proximal location and severe clot extent in first diagnosed left lower extremity DVT.